Economic Self-Efficacy Model and Islamic Education at The People's Instruction of Sumberpucung Malang - Ahmad Ma'ruf (Universitas Yudharta Pasuruan, 2021)
The model of economic self-efficacy and Islamic education is an important role in determining economic literacy policies in Pesantren Rakyat, This research uses a case study research method which is a qualitative research procedure, This research explores real life, good contemporary limited system case, as well as a limited variety of systems, The research location is at the Sumberpucung People's Islamic Boarding School, Malang. The object of the research: Caregivers, Administrators, and Heads of economic empowerment programs which are the main subjects. And extracting data using interviews, observations, documentation studies. The data analysis technique uses interactive model analysis, namely: data reduction, data presentation and conclusion drawing. The results of research on economic self-efficacy models and Islamic education in Islamic boarding schools, is in the context of realizing economic students and religious economists, realize independent students and students' independence in increasing Economic Self-Efficacy. And to support Islamic education in increasing the resources of educators, students and realizing a populist and dignified administrator.